The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.1007/s00276-015-1589-2
|View full text |Cite
|
Sign up to set email alerts
|

Experimental determination of the elbow’s center of rotation using the VICON™ optoelectronic motion capture system

Abstract: This study has validated a dynamic, non-invasive, and accurate method for locating the elbow's center of rotation. This preliminary study thus found a different center of rotation of the one in the middle of the trochlea previously thought. This could lead us to reflect on the designs of our prostheses to reduce the mechanical stresses and the risk of loosening.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
3
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 29 publications
1
3
0
Order By: Relevance
“…This represents the closeness of changing patterns. The MATLAB plot validates that the area involved during motion between double four-bar configuration's instantaneous center with elbow positions are identical, which lies under the reported value of the cross-sectional area of the instantaneous center of elbow joint at the lateral view (sagittal plane) [23,24]. The prototype of the designed configuration coupled with human limb is fabricated as shown in Figure 7, which shows the task performance while staying comfortable in movement, i.e., with least misalignment.…”
Section: Validationsupporting
confidence: 63%
See 2 more Smart Citations
“…This represents the closeness of changing patterns. The MATLAB plot validates that the area involved during motion between double four-bar configuration's instantaneous center with elbow positions are identical, which lies under the reported value of the cross-sectional area of the instantaneous center of elbow joint at the lateral view (sagittal plane) [23,24]. The prototype of the designed configuration coupled with human limb is fabricated as shown in Figure 7, which shows the task performance while staying comfortable in movement, i.e., with least misalignment.…”
Section: Validationsupporting
confidence: 63%
“…Elbow joint rotation is a multi-axis joint rotation, i.e., the instantaneous center of rotation of elbow axis varies with the elbow flexion-extension movement. It is reported that, normally, 2.5 mm × 7.8 mm is the cross-sectional area of the instantaneous center of elbow joint at lateral view (sagittal plane) [23,24]. Elvire et al [24] reported in their paper that the center of rotation of the elbow is 7± 14 mm at distal, 4 ± 9 mm at lateral and 4 ± 10 mm at the anterior to medial epicondyle.…”
mentioning
confidence: 97%
See 1 more Smart Citation
“…1 Meanwhile, the non-invasive and non-irradiating optical motion capture technique offers an efficient approach to estimate joint kinematics using marker-based musculoskeletal models. 2 However, in most studies that used a marker-based elbow model, the forearm was treated as a rigid segment, 3,4 and the elbow was commonly defined as a joint of two independent degrees of freedom: elbow flexion-extension (F/E) and pronation/supination (P/S), ignoring the fact that relative motion exists between ulna and radius. Particularly for forearm P/S, previous studies mainly used a goniometer directly on the subject to measure the overall rotation of a stick which is held in the hand during P/S.…”
Section: Introductionmentioning
confidence: 99%